Past and present of total artificial heart therapy: a success story - Samak, Mostafa; Fatullayev, Javid; Sabashnikov, Anton; Zeriouh, Mohamed; Rahmanian, Parwis B.; Choi, Yeong-Hoon; Wippermann, Jens; Wahlers, Thorsten; Schmack, Bastian; Ruhparwar, Arjang; Dohmen, Pascal M.; Karck, Matthias; et al. (Medical science monitor. Basic research, 2015)
The totally artificial heart (TAH) is among the most prominent medical innovations of the 21st century, especially due to the increasing population with end-stage heart failure. The progressive course of the disease, its resistance to conventional therapy, and the scarcity of hearts available for transplantation were the prime impetus for developing a TAH, especially when other options of mechanical circulatory assist devices are exhausted. In this review, we narrate the history of TAH, give an overview of its technology, and address the pros and cons of the currently available TAH models in light of published clinical experience.